PELATIHAN PENGELOLAAN INSTAGRAM JURNALISME ONLINE BAGI REMAJA PASCA GEMBA BUMI DI CIHERANG - Paramita, Sinta (Jurnal Serina Abdimas, 2023)
In December 2022, the Faculty of Communication Sciences, Tarumanagara University, in collaboration with the Institute for Research and Community Service (LPPM) of Tarumanagara University, held Community Service activities for victims of the earthquake disaster that occurred in Cianjur, Bogor, in November 2022. In this activity, the Untar Fikom Team had the opportunity to provide training related to disaster journalism for teenagers. From this activity, four teenagers (Ciherang Youth Journalism Team) will manage Instagram from the activities they carried out while participating in the Untar PKM Program and upload information about what happened. in refugee areas and others. However, the Ciherang Youth Journalism Team is still experiencing problems regarding managing Instagram after the disaster victim management process is complete and what material should be uploaded next. It can be seen from the uploads on Instagram @cianjurpkm that they have yet to upload information regularly, and the material uploaded is monotonous or only reposts information from other media, as well as upload criteria that do not meet the standards of journalism. Based on this information, the Tarumanagara University Faculty of Communication Sciences team plans to carry out further mentoring activities to provide refresher information, knowledge, and insight to the Ciherang Youth Journalism Team in managing Instagram. With the theme Instagram Management Training for Online Journalism for Teenagers After the Earthquake in Ciherang, it is hoped that the Ciherang Youth Journalism Team can provide various information and manage Instagram according to Online Journalism standards. The result of this activity is that the Team provides input regarding the development of other content regarding daily activity content or MSME activities that can be developed further. ABSTRAK Pada Bulan Desember 2022 Fakultas Ilmu Komunikasi Universitas Tarumanagara bekerja sama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Tarumanagara menyelenggarakan kegiatan Pengabdian Kepada Masyarakat untuk korban bencana gempa bumi yang terjadi di Cianjur Bogor pada bulan November 2022 lalu. Pada kegiatan tersebut Tim dari Fikom Untar berkesempatan untuk memberikan pembekalan terkait jurnalisme bencana untuk remaja, dari kegiatan tersebut diperoleh empat remaja dengan sebutan (Tim Jurnalisme Remaja Ciherang) yang akan mengelola Instagram dari kegiatan yang mereka jalani selama mengikuti Program PKM Untar dan mengunggah informasi yang terjadi di daerah pengungsian dan lain-lain. Namun hingga saat ini Tim Jurnalisme Remaja Ciherang tersebut masih mengalami kendala terkait pengelolaan Instagram tersebut selanjutnya setelah proses penanggulangan korban bencana selesai, dan materi apa yang harus diunggah selanjutnya. Terlihat dari unggahan di Instagram @cianjurpkm yang belum secara rutin mengunggah informasi, dan materi yang diunggah monoton atau hanya melakukan repost informasi dari media lain, serta kriteria unggahan yang belum memenuhi standar sebagai Jurnalisme. Atas informasi tersebut Tim dari Fakultas Ilmu Komunikasi Universitas Tarumanagara berencana melakukan kegiatan pendampingan selanjutnya untuk memberikan penyegaran informasi, pengetahuan dan wawasan kepada Tim Jurnalisme Remaja Ciherang dalam pengelolaan Instagram. Dengan tema Pelatihan Pengelolaan Instagram Untuk Jurnalisme Online Bagi Remaja Pasca Gempa Bumi Di Ciherang, diharapkan Tim Jurnalisme Remaja Ciherang dapat memberikan informasi yang beragam dan dapat mengelola Instagram sesuai standar Jurnalisme Online. Hasil dari kegiatan tersebut adalah Tim memberikan masukan terkait pengembangan konten yang lain terkait konten kegiatan sehari-hari atau kegiatan UMKM yang dapat dikembangkan selanjutnya.